Al-Khawarizmi: A Muslim Scientist Who Discovered Algorithms And Their Influence In The Development Of Modern Computation - Saputra, Hardika (Lembaga Penelitian dan Pengabdian kepada Masyarakat Institut Studi Islam Sunan Doe, 2023)
The algorithm discovered by Al Khawarizmi is a result of thinking that makes something that was impossible in modern science, possible today. In the book “The Advent of the Algorithm: The Idea that Rules the World” by David Berlinski, it is stated that there are two extraordinary ideas, calculus and algorithm. An algorithm is a systematic logical steps to solve a problem, which is composed and designed logically and systematically. The key element in an algorithm is its logical consistency. This is because an algorithm must be logical and its truth value (true or false) can be determined. An algorithm can also be defined as sequential steps in performing certain tasks. The advancement of modern computer technology today cannot be denied thanks to the contribution of algorithms. A computer programmer will undoubtedly always use algorithms in creating and developing their programs. Algorithms play a very important role in the development of computer technology, especially computer programs.